2011
DOI: 10.1016/j.profoo.2011.09.118
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Fields – assisted vinification

Abstract: Pulsed Electric Fields (PEF) treatments can be profitably applied as pretreatment to the extraction process from vegetable tissues, in order to increase the release of valuable compounds. In the present work we propose to apply PEF treatments during the vinification process for the permeabilization of the grape skins, in order to increase the polyphenolic content after maceration of red wines made from four Italian grape varieties, Aglianico, Piedirosso, Nebbiolo and Casavecchia. Prior to the fermentation/mace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Improving the degree of extraction of polyphenols during the maceration-fermentation stage of red winemaking has been one of the most widely investigated applications of pulsed electric fields (PEF) in recent years. Several research groups working with different grape varieties have demonstrated that a PEF treatment applied to grapes before the maceration-fermentation stage allows for a reduction of the contact time of grape skins with the fermenting must, or helps to obtain wines with higher polyphenolic content [2][3][4][5][6]. This effect is attributed to a phenomenon called electroporation, which involves an alteration of cell membrane permeability as a consequence of the application of an external electric field [7].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the degree of extraction of polyphenols during the maceration-fermentation stage of red winemaking has been one of the most widely investigated applications of pulsed electric fields (PEF) in recent years. Several research groups working with different grape varieties have demonstrated that a PEF treatment applied to grapes before the maceration-fermentation stage allows for a reduction of the contact time of grape skins with the fermenting must, or helps to obtain wines with higher polyphenolic content [2][3][4][5][6]. This effect is attributed to a phenomenon called electroporation, which involves an alteration of cell membrane permeability as a consequence of the application of an external electric field [7].…”
Section: Introductionmentioning
confidence: 99%
“…López-Giral et al [20] found an increase in the content of specific polyphenols such as gallic acid (24%), caffeic acid (48%) and rutin (141%) after PEF pretreatment of red grapes of different varieties. A comparison of enzyme treatment and PEF treatment with regard to the impact on the extraction process was done by Donsì et al [21] and revealed that for some of the investigated varieties, the enzyme treatment showed more pronounced effects. In contrast, Puértolas et al [22] stated that the extraction of phenolic compounds from red grape mash after PEF treatment was more effective than the addition of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Non-antioxidant compounds in wine (amino acids, uronic acids) may cause interferences and influence the estimated values of antioxidant capacity. Donsì et al (2011) have evaluated the effect of PEF treatment applied to four varieties of grapes in Italy in respect to antioxidant activity (by DPPH method) and have obtained a wine with a high antioxidant capacity (+40%).…”
Section: The Evaluation Of Antioxidant Capacity Of Peftreated and Untmentioning
confidence: 99%
“…The use of pulsed electric field (PEF) has been studied in specialized literature, leading to the conclusion that it contributes to increased efficiency due to the combination of the pressure effect and electroosmosis (Delsart et al, 2014;Donsì, Ferrari, Fruilo, & Pataro, 2011;GardeCerdán et al, 2013;Puértolas, López, Condón, Álvarez, & Raso, 2010a). PEF technology as a pretreatment step in winemaking technology has great potential in microbial control in wines.…”
Section: Introductionmentioning
confidence: 99%